Chaotic dynamics at cyclotron resonances - Buts, V.A.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2017)
Mechanisms and criteria for the transition to chaotic dynamics of particles and fields under conditions of electron cyclotron resonances (ECR) are considered. It is shown that the known conditions for the onset of dynamic chaos of charged particles in external electromagnetic fields require careful use. The mechanism of the appearance of regimes with dynamic chaos has been discovered and described, even under conditions of isolated cyclotron resonance. Anomalous sensitivity of particle dynamics to external fluctuations is described. It is shown that the higher moments of particle dynamics can play a significant role. In this case, the usual diffusion equations require a revision.